Cognitive linguistic approaches to teaching vocabulary and phraseology - Boers, Frank (Mouton de Gruyter, 2008)
Includes bibliographical references and index; How cognitive linguistics can foster effective vocabulary teaching -- Using conceptual metaphors and metonymies in vocabulary teaching -- Conceptual metaphoric meaning clues in two idiom presentation methods -- How cognitive linguistic motivations influence the learning of phrasal verbs -- A discovery approach to figurative language learning with the use of corpora -- Variables in the mnemonic effectiveness of pictorial elucidation -- Reasoning figuratively in early EFL -- Translating the senses -- What bilingual word associations can tell us -- Factors which influence the process of collocation -- The notion of boundedness/unboundedness in the foreign language classroom -- Structural elaboration by the sound (and feel) of it -- A quantitative comparison of the English and Spanish repertoires of figurative idioms -- From empirical findings to pedagogical practice